Extended Reality-Assisted Surgery as a Surgical Training Tool: Pilot Study Presenting First HoloLens-Assisted Complex Penile Revision Surgery. Issue 10 (8th September 2022) - Quesada-Olarte, Jose; Carrion, Rafael E.; Fernandez-Crespo, Raul; Henry, Gerad D.; Simhan, Jay; Shridharani, Anand; Carrion, Rafael E.; Hakky, Tariq S.
ABSTRACT: Background: Extended reality-assisted urologic surgery (XRAS) is a novel technology that superimposes a computer-generated image on the physician's field to integrate common elements of the surgical process in more advanced detail. An extended reality (XR) interface is generated using optical head-mounted display (OHMD) devices. Aim: To present the first case of HoloLens-assisted complex penile revision surgery. Methods: We describe our pilot study of HoloLens-assisted penile revision surgery and present a thorough review of the literature regarding XRAS technology and innovative OHMD devices. Outcomes: The ability of XRAS technology to superimpose a computer-generated image of the patient and integrate common elements of the surgical planning process with long-distance experts. Results: XRAS is a feasible technology for application in complex penile surgical planning processes. Clinical Translation: XRAS and OHMD devices are novel technologies applicable to urological surgical training and planning. Strengths and Limitations: Evidence suggests that the potential use of OHMD devices is safe and beneficial for surgeons. We intend to pioneer HoloLens technology in the surgical planning process of a malfunctioning penile implant due to herniation of the cylinder. This novel technology has not been used in prosthetic surgery, and current data about XRAS are limited. Conclusion: OHMD devices are effective in the operative setting. Herein, we successfully demonstrated the integration of Microsoft HoloLens 2 into a penile surgical planning process for the first time. Further development and studies for this technology are necessary to better characterize the XRAS as a training and surgical planning tool.